Nonasaccharide Inhibits Intrinsic Factor Xase Complex by Binding to Factor IXa and Disrupting Factor IXa–Factor VIIIa Interactions - Xiao, Chuang; Zhao, Longyan; Gao, Na; Wu, Mingyi; Zhao, Jinhua (Thrombosis and Haemostasis, 2019)
A nonasaccharide (FG9) derived from natural fucosylated glycosaminoglycan (FG) is identified as a selective intrinsic factor Xase complex (FIXa-FVIIIa-Ca2+-phospholipid, FXase) inhibitor that possesses potential inhibition of venous thrombus in rats and shows negligible bleeding risk. The mechanism and molecular target of the nonasaccharide for intrinsic FXase inhibition were systematically investigated and compared with low molecular weight heparin (LMWH). Our results showed that FG9 dose-dependently inhibited FX activation by intrinsic FXase complex in a noncompetitive inhibition pattern, where the apparent affinity for FG9 was approximately 1.8-fold higher than that for LMWH. FG9 displayed no inhibitory effect on the activity of FIXa/phospholipid, and did not affect the decay rate of FVIIIa activity. FG9 reduced the apparent affinity of FIXa for FVIIIa in a dose-dependent manner, and accelerated the decay of intrinsic FXase complex activity. FG9 bound to FIXa with high affinity and the FIXa binding sites of FG9 were overlapped with that of LMWH, and the ability of FG-derived oligosaccharides to bind FIXa required the minimum 9 degrees of polymerization. FG9 derivatives were prepared and their structures were confirmed by one-dimensional/two-dimensional nuclear magnetic resonance. Structure–activity relationship studies showed that carboxy reduction significantly weakened its anti-FXase activity and binding affinity to FIXa, while the effects of carboxyl ethyl esterification and deacetylation were relatively weaker. Overall, our results suggest that the nonasaccharide FG9 strongly inhibits intrinsic FXase complex activity via binding to FIXa and disrupting FIXa–FVIIIa interactions, and the free carboxyl groups of FG9 are required for its potent anti-FXase activity.
Keywords: nonasaccharide from fucosylated glycosaminoglycan; intrinsic factor Xase complex; factor IXa; anticoagulant